Fabrication of Advanced Cement Mortar for Building Anti-Bacterial Applications - Othman, Farhad M.; Abdul-hamead, Alaa A.; Hmeed, Noor A. (Al-Khwarizmi Engineering Journal, 2019)
In this research, we have added nano anatase TiO2 as a partial replacement of Portland cement by a weight percentage of (0.25 to 1%) for the development of properties for protection against bacteria. The control mix was made by using "the cement to sand" proportion about (1: 2.75) with the "water to cement" proportion of (0.5) to study the structure, porosity, water absorption, density, mechanical properties, as well as anti-bacterial behavior. Inspections have been done such as scanning electron microscopy (SEM), and atomic force microscope (AFM) for mortar. Experimental results showed that after the addition of Nano powders in cement mortar, the structural properties improved significantly with the development of hydration of cement mortar at early age, reduction of porosity and the increase of density as well as enhancement in compressive and anti-bacteria properties that make the preparation of nano material very suitable for protection against bacteria.